Determination of Rifampicin, Isoniazid, Pyrazinamide and Ethambutol Hydrochloride in 4FDC Tablet by FTIR Spectrophotometry in Combination with Multivariate Calibration - Kurniati, Zakiah; Riyanto, Sugeng; Rohman, Abdul Abdul (Fakultas Farmasi, Universitas Gadjah Mada, 2016)
This study was aimed to develop a fast, inexpensive, simple, and not involving hazardous reagent for the determination of rifampicin (RIF), isoniazid (INH), pyrazinamide (PZA) dan ethambutol hydrochloride (ETH) in 4FDC tablet based on infrared spectrophotometry in combination with chemometrics of partial least square (PLS) calibration. The analytical procedure involves three steps, namely calibration, validation and sample assay. The multivariate calibration model is evaluated by determining the precision and accuracy parameters, as suggested by IUPAC. The results showed that the optimized wavenumber range for the determination of RIF was the combined wavenumbers of 433 – 1552 cm-1 and 1756 – 3412 cm-1, the wavenumber of 433 – 873 cm-1 was selected for quantification of INH, 1714 – 2756 cm-1 for PZA, and 1552 – 2970 cm-1 for ETH. The predicted residual error sum of square (PRESS) values of RIF, INH, PZA and ETH contents were 0.00392%, 0.011724%, 0.007604%, and 0,003368%, respectively. The root mean square error of prediction (RMSEP) values obtained for analysis of RIF, INH, PZA and ETH were 0.01979%, 0.03424%, 0.027575% and 0.018351%, respectively. The values of coefficient of determination (R2) for the relationship between actual values of these drugs and calculated values of these drugs using FTIR spectroscopy were 0.990, 0.977, 0.992 and 0.998 for RIF, INH, PZA and ETH, respectivelty. The developed method was succesfully applied for the determination of 4FDC tablet. The contents of RIF, INH, PZA and ETB in 4FDC tablets were in agreement with those specified in monograph of Indonesian Pharmacopeia.Keywords: infrared spectrophotometry, rifampicin, isoniazid, pyrazinamide, ethambutol hydrochloride, partial least square.